Observing Amid the Anthropocene: An Excursus in Methodology or the How of Inquiry - Gilson, Cedric Charles (Anthropocenes, 2022)
Amid complex issues like those of the Anthropocene, choice of methodology in inquiry is critical to assure the validity of an inquiry’s conclusions. Confidence in its success can be gained initially through the exercise of introspection. More importantly, the complexity of inquiry needs to be commensurate with that of the subject. Since ανθρωπός (anthropos) is the cause of environmental deterioration, inquiry must be thematically anthropological and future-orientated towards the evolution of mankind amid technological advance. These themes promulgate modes of observation from which an inquirer can observe empirically. Eventually, with the need for increasing complexity of inquiry, the abilities of such a method of study become exhausted, with epistemology and empiricism consequent casualties. In a leap of theory and inspired by Haraway’s conjecture of the cyborg in posthumanism, the approach then privileges the ontological so that observers instead become beings and exploration of the relationship to the Anthropocene of the human qua human, qua transhuman and so on, can be pursued by moving inside. With the inherent sacrifice of the observing outside(r), the inquirer is deprived of communication. Academe then substitutes as the cerebral, transcendent, inquirer/communicator and survivor of posthumanism amongst beings, sans pareil, through publication and education. Some consequences of this are explored. The author borrows gratefully from Niklas Luhmann’s characterisation of observation in social systems. His assertions concur with the effects of the transformations proposed in the study, including the autopoiesis of the newly-theorised beings.